Uncovering the role of defective HIV-1 in spreading viral infection. (April 2015) - Arenaccio, Claudia; Manfredi, Francesco; Anticoli, Simona; Chiozzini, Chiara; Federico, Maurizio
ABSTRACT : Defective HIV-1 genomes populate blood cells of HIV-1 infected patients, especially during HAART treatment. They can express viral proteins which, if released, may induce bystander effects favoring viral spread. Here, we review recent literature regarding the effects of extracellular HIV-1 proteins which can act as effectors of transcriptionally active, defective HIV-1, including Gag p17, Env gp120, Vpr, Tat and Nef. It has been very recently described that, different to the other HIV products, the bystander effects of Nef can be mediated by exosomes, that is, nanovesicles constitutively released by all cell types. Exosomes from Nef-expressing cells induce cell activation and HIV-1 susceptibility in resting CD4 + T lymphocytes in a TNF-α-dependent way. This mechanism likely contributes to virus persistence in HAART-treated patients.